A survey on localization techniques in wireless sensor networks - Bharathi Priya, C; Sivakumar, S (International Journal of Engineering and Technology, 2017)
Wireless Sensor Networks (WSNs) are a kind of ad-hoc networks where the nodes in the network have sensors on board and can sense different phenomena around the sensors deployed in the field. WSNs became very popular due to its diverse nature of applications including Cyber-Physical Systems (CPS), Precision Agriculture, Disaster relief & Rescue operation, Object Tracking in terrestrial environment, Health care application to monitor the physical parameters of a human, space application etc. Most applications use the location information of a sensor node as an inherent characteristic. Location information is mandatory in order to identify in which spatial coordinate the sensor data originates. Broadly, the localization techniques are classified as: range based and range free methods. Hence study of localization techniques for Wireless Sensor Networks is highly significant today for different kind of applications. This paper gives an overview on survey of localization techniques in Wireless Sensor Networks and its current significance.